Knowledge and Perception of Nigerian University Undergraduates about the Risks Associated with using Commercial Motorcycle for Transportation (2017)
Background and Purpose of Study: Commercial motorcycle is a popular mode of mass transportation in Nigeria, which despite its acknowledged benefits has been associated with health and social problems. It is embraced largely by young Nigerians, including university undergraduates who have not been well studied with respect to this mode of transportation. We determined the proportion of undergraduates of a Nigerian university regularly using commercial motorcycle. Level of knowledge and perception of risks associated with usage and some factors that may influence choice of commercial motorcycle were also investigated. Methods: This cross-sectional survey was conducted among Nigeria premier University of Ibadan undergraduates, recruited from their halls of residence using consecutive sampling technique. A self-administered questionnaire was hand distributed to obtain information on the respondents' socio-demographic variables, knowledge and perception of risks associated with using commercial motorcycle for transportation. Descriptive statistics were calculated and Chi- square test was used as inferential statistics at á = 0.05. Results: Among the 1000 respondents, 75% regularly used commercial motorcycle for transportation. A statistically significant association was found between gender and the knowledge of risks (p? 0.001) and also between age and the perception of risks associated with using this mode of transportation. However, there was no significant difference in the knowledge (p=0.03 and perception of risks (p=0.97) associated with using commercial motorcycle for transport between users and non- users. Conclusions: Respondents had limited knowledge and low perception of the risks associated with using commercial motorcycle for transport. Strategies should be put in place to educate these youths on the risks associated with using commercial motorcycle for transport.